2014
DOI: 10.2174/13816128113199990541
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression and Altered Methylation of Syncytin-1 Gene in Human Placentas Associated with Preeclampsia

Abstract: Syncytin-1 is a protein coded by a human endogenous retrovirus (HERV) gene of the HERV-W family (HERVWE1). Syncytin- 1 mediates formation of syncytiotrophoblasts through fusion of cytotrophoblasts, a hallmark of terminal differentiation of placental trophoblast linage. Syncytin-1 also possesses nonfusogenic functions and regulates cell cycle progression. While decreased syncytin-1 expression and syncytium deficiency are considered important pathological changes in preeclampsia, the molecular mechanism(s) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…40 Increased DNMT1 and DNMT3B correlate with decreased expression of syncytin-1, GATAD1, and HLA-G in preeclamptic placentas, which are key factors in trophoblast. [41][42][43] These findings stimulate interest in investigating the roles of DNMT1 and DNMT3B in PE in future studies.…”
Section: Discussionmentioning
confidence: 89%
“…40 Increased DNMT1 and DNMT3B correlate with decreased expression of syncytin-1, GATAD1, and HLA-G in preeclamptic placentas, which are key factors in trophoblast. [41][42][43] These findings stimulate interest in investigating the roles of DNMT1 and DNMT3B in PE in future studies.…”
Section: Discussionmentioning
confidence: 89%
“…PE is diagnosed based on arterial hypertension and proteinuria in pregnancy (Wilson et al 2003). Many reports have shown decreased expression and aberrant localization of syncytin 1 in PE placentas compared with healthy controls (Lee et al 2001, Chen et al 2006, Langbein et al 2008, Vargas et al 2014, Zhuang et al 2014. Chiang et al (2009) showed decreased levels of GCM1, syncytin 1 and placental growth factor, which are all crucial for syncytiotrophoblast formation and placental vasculogenesis in PE placentas.…”
Section: Syncytin 1 (Herv-w; Ervw-1) and Human Placentationmentioning
confidence: 99%
“…Syncytins Outcome Zhuang et al (2014) Syncytin 1 Hypermethylation of syncytin 1 promoter in PE compared with normal placentas. Increased DNMT1 and DNMT3B3 mRNA and protein levels in PE placentas.…”
Section: Referencementioning
confidence: 99%
“…It has been known that hGCMa, a zinc-containing transcription factor, regulates the syncytin-1 gene, which takes part in cell cycle progression (Zhuang et al, 2014). FBXW2 was found to promote the degradation of hGCMa by ubiquitination (Yang, Yu, 2005).…”
Section: Roles Of Fbxw Sub-family In the Regulation Of Cell Cyclementioning
confidence: 99%